Efek Seduhan Tepung Daun Kelor terhadap Kadar Glukosa Darah Puasa Tikus Diabetes Melitus - Ahmad Andi Setiawan; Uun Ratriantari; Adhiningsih Yulianti (Politeknik Negeri Jember, 2023)
Diabetes Mellitus (DM) is a group of metabolic disease with characteristic which caused by abnormal insulin secretion, insulin process or both of it. Moringa is a plant which have high bioactive compound. Flavonoid total content of a moringa powder is a 473,3 mg/100 g. The study aimed to analyze the efffect Steep of Moringa leaf flour on fasting blood glucose levels of diabetic rats. Experimental with pretest posttest control group design was used in this study. A total of 15 male Sprague dawley rats who obtained LPPT 4 Gadjah Mada University at Yogyakarta was selected as research samples. Rats were assigned to three experimental group (negative control group, positive control group, and treatment group). Negative control group (n=5) was given intraperitoneal injection with phosphat buffer saline (PBS), positive control group (n=5) was given intraperitoneal injection with single low dose STZ (30mg/kgBB), and treatment group (n=5) was given intraperitoneal injection with single low dose STZ (30mg/kgBB) and moringa leaf flour steeping at 3,75 g/kgBB. Fasting blood glucose levels was analyzed using GPO-PAP methods after 3 days STZ-induced rats. Data analysis used Kruskal wallis and One Way Anova test. Pretest and posttest fasting blood glucose levels had a significant difference between groups (p=0.008 and p=0,000). Moringa leaf flour steeping to decrease fasting blood glucose levels of diabetics rats.